Rushing waters [large type] : a novel - Steel, Danielle (Random House Large Print, 2016)
"A 38-year-old American interior designer based in London and her independent-minded 74-year-old architect mother; a British investment banker in New York to see his ex-wife and young children; a resident ER doctor who experienced Hurricane Sandy when she was a medical student; two young men, 21-year-old NYU students; their friends; and others are thrust together when a major hurricane descends upon New York City and wreaks unimaginable chaos and devastation. Yet through the darkness, these characters form unlikely new friendships and together, manage to find hope and revitalization"--